STRATEGI PELESTARIAN LONGGO SEBAGAI WARISAN BUDAYA GORONTALO DI SMA NEGERI 2 GORONTALO - Sunarsi N. Dai; Habiba Hulopi; La Ode Sarudin (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2023)
The people of Gorontalo have many cultural heritages, one of which is longgo. Longgo is a martial art that has existed since ancient times. Until now, it is still maintained even though only controlled by certain groups in Gorontalo society. Longgo has noble values that can provide strengthening character education for the younger generation. However, in reality, the younger generation of Gorontalo do not know this traditional martial art anymore. This research uses qualitative research methods. The purpose of this study is to: describe the existence of longgo among the people of Gorontalo, and the efforts that can be made in preserving longgo as a cultural heritage full of noble values. The benefits of this research are expected to: broaden knowledge about the local wisdom of longgo martial arts and procedures for its implementation in Gorontalo society, add reinforcement for Gorontalo people to preserve longgo, make the results of this research part of a joint effort in realizing government policies in supporting local cultural preservation. The results of this research indicated that longgo will be preserved if all the people in Gorontalo protect and promote this martial art seriously.